Pengaruh Kualitas Pelayanan, Harga Dan Promosi Terhadap Kepuasan Konsumen Bus Pariwisata Merpati Trans - Putri, Mustikawati Setyo, Drs. Agus Mugorobin, M.M (2017)
ABSTRACT This study aims to analyze the influence of service quality, price and promotion of customer satisfaction of Merpati Trans Tourism Bus. Based on the results of this study is expected to be useful as input and information material for the Transpati Mer Tourism Bus about the factors that affect customer satisfaction such as service quality, price, and promotion in order to be able to meet the criteria of customer satisfaction. Hypothesis testing in this research using regression analysis tool with t test, F test and coefficient of determination (R2). Population of this research is all customer of Bus Tourism Merpati Trans. The sample in this research is 100 customers of Trans Pigeon Tourism Bus.Based on the result of research known that influence of service quality, price and promotion to consumer satisfaction of Bus Merpati Trans Tourism known that service quality have significant influence to consumer satisfaction of Bus Tourism Merpati Trans, so H1 accepted. Price significantly influence on consumer satisfaction Bus Merpati Trans Tourism, so H2 received promotion significant effect on consumer satisfaction Bus Tourism Merpati Trans, so H3 accepted. Keywords: service quality, price, promotion, consumer satisfaction.